ORANG-ORANG YANG BERDAMAI DENGAN KEMISKINAN - Effendi, Chairil (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Orang-orang Biasa (Ordinary People ¸ 2019) is the second latest novel authored by Andrea Hirata before Guru Aini (2020). Similar to his other literary works, this novel employs the Malay society"™s sociocultural background as well, especially in Belantik city, Belitong. What is unique from this novel, which distinguishes it from Hirata"™s other novels, drives this research. The data used are discourse and story: discourse manifests in language as the primary symbolic system, meanwhile story manifests in literary dimension as the second symbolic system, composed of utterances, actions, and events in words. Using the method of heuristic and hermeneutic reading, and also textual analysis using sociological and anthropological methods, this research implies several findings. This novel narrates the foolishness and brilliance of lower class, marginalized society, but also displays their high social loyalty and morality. This group can hardly access and seek the opportunity to do businesses, bank credits, and also study in higher education"”despite the intelligence modality they possess. Tragically, this group of society will always be the victims of oppressive and despotic behaviors by those who possess political and economic power.Keyword: Andrea Hirata, Ordinary People, Heuristic and Hermeneutic  AbstrakOrang-orang Biasa (Ordinary People ¸2019) merupakan novel kedua terakhir karya Andrea Hirata sebelum Guru Aini (2020). Sebagaimana karya-karyanya yang lain, novel ini pun menggunakan latar sosial budaya masyarakat Melayu, khususnya di Kota Belantik, Belitong, tetapi dengan fokus yang berbeda. Kekhasan itulah yang melatarbelakangi dilakukannya penelitian ini. Datanya berupa discourse dan story: discourse berupa bahasa sebagai sistem simbol pertama, sedangkan story berupa dunia sastra sebagai sistem simbol kedua yang berisi ucapan, tindakan, dan peristiwa dalam kata-kata. Dengan menggunakan metode pembacaan heuristic dan hermeneutic, serta analisis teks dengan pendekatan metode sosiologis dan antropologis, diperoleh pemahaman sebagai berikut. Novel ini mengisahkan kebodohan sekaligus kecerdikan masyarakat bawah, yang terpinggirkan, tetapi memiliki rasa kesetiakawanan sosial dan moralitas yang tinggi. Kelompok masyarakat ini tidak memiliki aksesibilitas yang luas untuk berdagang, meminjam kredit bank, juga kuliah di perguruan tinggi"”meskipun memiliki modal intelektualitas yang tinggi. Tragisnya, kelompok masyarakat ini selalu menjadi korban tindakan semena-mena kelompok masyarakat lain yang memiliki kekuasaan politik dan kekuatan ekonomi.Keyword: Andrea Hirata, Orang-orang Biasa, Heuristic dan Hermeneutic